2023
DOI: 10.3389/fendo.2023.1051592
|View full text |Cite
|
Sign up to set email alerts
|

Association between skipping breakfast and prediabetes among adolescence in Japan: Results from A-CHILD study

Abstract: ObjectiveAdolescents with prediabetes are at high risk of developing type 2 diabetes in later life. It is necessary to identify risk factors for prediabetes in adolescents. This study aimed to examine the association between skipping breakfast and prediabetes among adolescents in Japan.Study designWe used the population-based cross-sectional data of eighth grade in junior high school students from the Adachi Child Health Impact of Living Difficulty (A-CHILD) study conducted in Adachi City, Tokyo, Japan, in 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Breakfast is commonly considered to be the most important meal of the day although many people skip it. Based on current findings, skipping breakfast can be a risk factor for impaired glucose metabolism, leading to prediabetes [ 37 ]. Furthermore, a systematic review and meta-analysis of prospective cohort studies based on 96,175 participants and 4935 cases indicated that breakfast skipping is associated with an increased risk of T2D [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Breakfast is commonly considered to be the most important meal of the day although many people skip it. Based on current findings, skipping breakfast can be a risk factor for impaired glucose metabolism, leading to prediabetes [ 37 ]. Furthermore, a systematic review and meta-analysis of prospective cohort studies based on 96,175 participants and 4935 cases indicated that breakfast skipping is associated with an increased risk of T2D [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are many studies currently focusing on the adverse effects of skipping breakfast on the physical health. For example, previous studies demonstrated that skipping breakfast was associated with prediabetes [ 13 ] and gynecologic disorders [ 14 ], etc. Interestingly, skipping breakfast has also been reported to be associated with negative emotions [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%